A Mubādalah Based Legal–Cultural Model of Mak Dijuk Siang in the Lampung Pepadun Megou Pak Community for Strengthening Family Resilience in Indonesia - M. Anwar Nawawi; Chalawah Ummy Sa’diyah (Journal of Islamic Mubadalah, 2025)
This article examines the application of customary law regarding the prohibition of divorce (Mak Dijuk Siang) within the Lampung Pepadun customary community, where this norm functions as a mechanism for resolving household conflict. The central issue arises from indications that the prohibition generates marital disharmony by limiting the range of conflict-resolution options available to couples. The purpose of this article is to analyze (1) how Mak Dijuk Siang is implemented as a binding customary norm, (2) its social and emotional implications for family stability, and (3) the formulation of a culture law integration model grounded in the principle of reciprocity. Employing a qualitative, socio-legal approach informed by the mubādalah framework, the study finds that Mak Dijuk Siang is enforced through nuwo adat, family deliberation, and formal customary mediation, reflecting the moral values of pi’il pesenggiri. While this rule reinforces social cohesion, it may simultaneously intensify domestic tensions. The integration of mubādalah ethics offers a more equitable reinterpretive model that strengthens family resilience. The recommendations call for improving customary institutional policies and enhancing the role of traditional leaders so that dispute-resolution mechanisms become more protective, reciprocal, and oriented toward sustaining family wellbeing.